Seamless teamwork : using Microsoft SharePoint technologies to collaborate, innovate, and drive business in new ways - Sampson, Michael (Microsoft Press, 2009)
"Take the lead - and deliver better results - by revolutionizing the way you and your colleagues communicate, collaborate, and coordinate everyday work. Dive in as the author, a collaboration expert, demonstrates how to inspire great teamwork using Microsoft SharePoint technologies. Discover the best practices that enable even far-flung teams to produce powerfully productive results - and apply them to your own projects!"--Jacket.